2013
DOI: 10.17576/pengurusan-2013-39-12
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Performance: Conventional versus Islamic

Abstract: Using CAMELS rating to measure bank performance, the present study compares the performance estimates for Islamic banks with conventional banks operating in Malaysia from 2008 to 2011. The present study further identifies the determinants affecting the performance of conventional and Islamic banks in Malaysia. Using a sample of 19 conventional banks and 16 Islamic banks, the results indicate that the levels of composite performance achieved by both conventional and Islamic banks in Malaysia are very similar. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Overall results are in confirmatory with the findings of (Alzghoul, 2015;Islam & Ashrafuzzaman, 2016;Kamaruddin & Mohd, 2013;Karapinar & Dogan, 2015b;Rozzani & Rahman, 2013) and (Jaffar & Manarvi, 2011;Kouser & Saba, 2012). They also found that Shariah compliance banks are better in managerial quality, liquidity, profitability and capital adequacy.…”
Section: Sensitivitysupporting
confidence: 90%
“…Overall results are in confirmatory with the findings of (Alzghoul, 2015;Islam & Ashrafuzzaman, 2016;Kamaruddin & Mohd, 2013;Karapinar & Dogan, 2015b;Rozzani & Rahman, 2013) and (Jaffar & Manarvi, 2011;Kouser & Saba, 2012). They also found that Shariah compliance banks are better in managerial quality, liquidity, profitability and capital adequacy.…”
Section: Sensitivitysupporting
confidence: 90%
“…Thus bank performance is critical for its survival. Studies that examine determinants affecting the bank performance, such as [2], do not clarification concerning the bank risk determinants existed in relation to performance.…”
Section: Introductionmentioning
confidence: 99%
“…We use CAR, ROA, ROE, NPF, FDR, and NB as independent variables. The independent variables are constructed based on previous studies (see, for example, Sufian & Noor, 2009;Ariyani, 2010;Ahmad & Noor, 2011;Sardar et al, 2011;Pambuko, 2016;Firdaus & Hosen, 2013;Mu'izzuddin & Isnurhadi, 2013;Rozzani & Rahman, 2013;Subandi & Ghozali, 2014;Lutfiana & Yulianto, 2015;Bisri, 2016;and Havidz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%